A laser-induced graphene-based flexible and all-carbon organic electrochemical transistor. Issue 14 (29th March 2023) - Ren, Guozhang; Fan, Hua; Zhang, Linrong; He, Shunhao; Zhu, Chengcheng; Gao, Kun; Zhang, Yulong; Wang, Junjie; Kang, Xing; Song, Yaxin; Gong, Zhongyan; Li, Gongqiang; et al.
Abstract : In this study we design and fabricate an all-carbon OECT by using laser-induced graphene (LIG) as the electrode, and high output performances are achieved because of the porous structure on the LIG surface. Abstract : As next-generation bioelectronic devices, organic electrochemical transistors (OECTs) have attracted great interest in health monitoring and early diagnosis because of their high sensitivity, easy integration, high flexibility, and light weight. However, costly gold electrodes fabricated by lithography are commonly used in traditional OECTs and the devices are usually composed of rigid materials, limiting their flexibility and cost effectiveness. To improve the flexibility and cost efficiency, we design and fabricate an all-carbon OECT by using laser-induced graphene (LIG) as the electrode. A high output performance is achieved because of the porous structure on the LIG surface. The obtained OECT has a high normalized transconductance of 30.1 ± 3.2 S cm −1 . In addition, our LIG-based OECT possesses high stability and flexibility. After being integrated with a microfluidic chip, the LIG-based OECT demonstrates sensitive detection of glucose in artificial sweat and on human skin. We envision that the simple and cost-effective LIG-based OECT will advance the development of flexible bioelectronics.